2011
DOI: 10.1111/j.1365-2028.2011.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Beehive fences as effective deterrents for crop-raiding elephants: field trials in northern Kenya

Abstract: Increasing elephant populations in Kenya since 1989 have been widely praised as a conservation success story. However, where elephants and agricultural land overlap, incidents of human-elephant conflict are on the increase. Wildlife managers and farmers are now trying different farm-based deterrents to keep elephants out of crops. Here, we present data on the effectiveness of a novel beehive fence deployed in a Turkana community of 62 communally run farms in Kenya. Specifically, 1700 m of beehive fences semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 24 publications
10
71
0
1
Order By: Relevance
“…In a two-year trial study of a various types of live fencing a communal farm community in Kenya, beehive fencing was found to be more effective at preventing elephant farm invasions than thorn bush barriers. Elephants entered crop fields at locations blocked by thorn bushes 31 times during the study compared to a single time where a beehive barrier was in place (King et al 2011).…”
Section: Opportunity-reducing Conservationmentioning
confidence: 99%
“…In a two-year trial study of a various types of live fencing a communal farm community in Kenya, beehive fencing was found to be more effective at preventing elephant farm invasions than thorn bush barriers. Elephants entered crop fields at locations blocked by thorn bushes 31 times during the study compared to a single time where a beehive barrier was in place (King et al 2011).…”
Section: Opportunity-reducing Conservationmentioning
confidence: 99%
“…In some cases, managing the 'pest' through ecological interactions with other animals can reduce costs and enhance benefits for farmers. For example, elephants avoid African honey bee (A. mellifera scutellata) hives, through fear of attack, and King et al (2011) showed how Kenyan farming communities used a fence of bee hives to keep crop-raiding elephants from damaging their crops, while also enhancing pollination services and gaining additional income from honey harvests.…”
Section: Activity Of a Single Animal Species Can Have Different Effecmentioning
confidence: 99%
“…For example, fences incorporating hives of dangerous African bees deterred crop-raiding attempting elephants from breaking through them [16]. Similarly, we implemented our research in a manner that mitigated nighttime crop-raiding [17].…”
Section: Discussionmentioning
confidence: 99%